Menganalisis Indeks Pembangunan Manusia (IPM), Inflasi, Serta Pengangguran Sebagai Upaya Penanggulangan Kemiskinan Indonesia - Seger Santoso; Windi Alfaisa (Master Manajemen, 2024)
This study aims to analyze the impact of the Human Development Index (HDI), inflation, and unemployment on poverty alleviation efforts in Indonesia. Poverty in Indonesia, affecting 24% of the total population, remains a serious issue in economic development despite various efforts by the government. This study employs a quantitative method with time series data analysis from 2015 to 2023. Data were obtained from the Central Bureau of Statistics (BPS) and the Coordinating Ministry for Economic Affairs of the Republic of Indonesia. The statistical tests used include descriptive analysis, classical assumption tests (multicollinearity, autocorrelation, heteroscedasticity, and normality), coefficient of determination test, and multiple linear regression analysis. The results show that the variables HDI, inflation, and unemployment have a significant impact on poverty levels. The coefficient of determination (R²) test indicates that 70.9% of the variation in poverty levels can be explained by these three independent variables. The partial hypothesis test (t-test) reveals that unemployment has the most significant impact on poverty compared to HDI and inflation. From this study, it can be concluded that improving HDI, controlling inflation, and reducing unemployment are crucial factors in poverty alleviation efforts in Indonesia. Therefore, a comprehensive and integrated approach from the government, private sector, and civil society is necessary to address poverty issues and enhance social welfare in Indonesia.